EXTH-100. EVALUATION OF PANOBINOSTAT PLASMA AND CEREBROSPINAL FLUID (CSF) PHARMACOKINETIC PROFILE FOLLOWING ADMINISTRATION OF THE CAPSULE FORMULATION FARYDAK® IN A NON-HUMAN (NHP) PRIMATE PRECLINICAL MODEL. (14th November 2022) - McCully, Cynthia Lester; Warren, Katherine; Zimmerman, Sara; Peer, Cody; Killoran, Kristin; Garcia, Rafael Cruz; Figg, William; Widemann, Brigitte
Abstract: Panobinostat is an HDAC inhibitor with dose-dependent pre-clinical activity against pediatric glioma. Reported pharmacokinetic (PK) profiles of panobinostat, including CSF penetration, have varied. We hypothesized that this variability resulted from the utilization of differing panobinostat formulations. For comparison to the USP grade powdered formulation PK profile formerly reported (Rodgers, et al., Cancer Chemother Pharmacol. 2020 Apr;85(4):827-830) a plasma and CSF PK study was conducted with panobinostat administered as the capsule formulation, Farydak®, utilizing the same non-human primate (NHP) model, study design, analytical methods, and analysis. METHODS: Three NHP previously developed for serial CSF access via a lateral ventricular CSF reservoir (n=2), or lumbar CSF port (n=1) received panobinostat orally (1.6 mg/kg, Human Dose Equivalent: 32 mg/m 2 ) followed by serial paired plasma and CSF sample collections from 0-72 hours. Samples were quantified by LC-MS/MS. PK parameters were determined via noncompartmental analysis. RESULTS: Mean plasma and CSF PK parameters Tmax (h), Cmax (nM), and AUCinf (h*nM/mg) are reported and compared to the corresponding PK parameters from the USP grade powdered formulation study formerly reported. Capsule Formulation: Plasma - Tmax : 5.3 □ 1.2, Cmax : 20 □ 1.9, AUClast : 14.5 □ 11.1, AUCinf : 15.2 □ 11.4 CSF - Tmax : 5.0 □ 3.6, Cmax : 1.7 □ 0.3, AUClast : 0.54 □ 0.47, AUCinf : unable to calculate Powdered Formulation – Mean PK of all dose levels formerly reported: Plasma -Tmax : 1.06 □ 0.13, Cmax : 1.27 □ 0.6, AUCinf : 7.7 □ 2.7 CSF - Cmax and Tmax : Unable to determine. Single quantifiable sample across all studies. AUCinf : unable to calculate. CONCLUSION: The plasma and CSF Tmax, Cmax, the plasma AUCinf, and the CSF AUClast for panobinostat were increased following oral administration of the capsule formulation of panobinostat, Farydak®, compared to USP grade powder formulation of the drug.